2009
DOI: 10.1080/14992020902931566
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in postlingually hearing-impaired adults: Choosing the most appropriate ear

Abstract: Choice of the most appropriate ear for CI in postlingually hearing-impaired adults is becoming more relevant as more patients are considered eligible for intervention. The aim of this study is to review factors that influence this choice and to formulate a flowchart. An extensive Medline search was performed. Factors can be divided into surgical, audiological, and patient factors. Surgical factors are anatomic variation and otological medical history. Both are divided in absolute and relative contraindications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In our opinion, one important prerequisite for the success of cochlear implantation in unilateral deafness is the careful selection of patients. In patients with profound bilateral hearing loss, the duration of deafness is one important factor influencing the outcome in speech comprehension (28). In conformity with these findings, patients with postlingually acquired unilateral deafness should be provided with a CI shortly after confirming the persistence of deafness.…”
Section: Discussionmentioning
confidence: 90%
“…In our opinion, one important prerequisite for the success of cochlear implantation in unilateral deafness is the careful selection of patients. In patients with profound bilateral hearing loss, the duration of deafness is one important factor influencing the outcome in speech comprehension (28). In conformity with these findings, patients with postlingually acquired unilateral deafness should be provided with a CI shortly after confirming the persistence of deafness.…”
Section: Discussionmentioning
confidence: 90%
“…Using only one HA on the future implanted ear was linked to a marginally greater reduction of CI speech performance than using only one HA on the ear contralateral to the implanted ear (0.64% per year of s/p HL vs 0.49%). Because general practice is to preserve the ear with the more efficient residual hearing [11], [28], [29], we may hypothesize that if the ear chosen to be implanted was the only one using a HA, the contralateral ear was profoundly deaf and probably presented with a much longer duration of s/p HL [27]. The central and peripheral auditory wiring might have been poorer in this case than when the HA was worn on the non-implanted ear.…”
Section: Discussionmentioning
confidence: 91%
“…It is likely that the actual choice of the side to implant was based on patients' reports rather than PTA. The ear with the better PTA is not always the ear with the more usable acoustic hearing, and the ear with the shortest duration of deafness is often preferred when aided performances are similar [27]. Preserving efficient residual hearing of the better ear (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…(2015) [20] reported significantly lower word repetition ability in patients with SSCD compared to those without it. However, the reference group and the SSCD group in their study showed a significant difference regarding the duration of hearing loss (249 versus 494 months), which is a known factor influencing the outcome of CI (van den roek and Dunnebier, 2009) [21]. They therefore accounted for the significance of the difference between the two groups being primarily due to a significantly longer duration of hearing loss in the SSCD group.…”
Section: Clinical Symptoms May Consist Of Conductive or Mixed Hearing...mentioning
confidence: 88%